If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 2(7 + -4n) + 2(2n + -2) -18 = (7 * 2 + -4n * 2) + 2(2n + -2) -18 = (14 + -8n) + 2(2n + -2) Reorder the terms: -18 = 14 + -8n + 2(-2 + 2n) -18 = 14 + -8n + (-2 * 2 + 2n * 2) -18 = 14 + -8n + (-4 + 4n) Reorder the terms: -18 = 14 + -4 + -8n + 4n Combine like terms: 14 + -4 = 10 -18 = 10 + -8n + 4n Combine like terms: -8n + 4n = -4n -18 = 10 + -4n Solving -18 = 10 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. -18 + 4n = 10 + -4n + 4n Combine like terms: -4n + 4n = 0 -18 + 4n = 10 + 0 -18 + 4n = 10 Add '18' to each side of the equation. -18 + 18 + 4n = 10 + 18 Combine like terms: -18 + 18 = 0 0 + 4n = 10 + 18 4n = 10 + 18 Combine like terms: 10 + 18 = 28 4n = 28 Divide each side by '4'. n = 7 Simplifying n = 7
| 8x-10+7x+70=180 | | 7x-1=4x-14 | | (1+i)(3+i)= | | 7x-3-4x=4x-1 | | 2x-45=21 | | 4x+6=-4+2x+20 | | 1089+b^2=2025 | | 6-7x-4=-36+5x-10 | | 4y+16x=180 | | -5(3v-6)=4(1-7v) | | 3x+12+2x+18=180 | | 2x-14=2x-13 | | -8x-9=3x+24 | | 4(-6-3x)=-4(x+6) | | 100n+3=104 | | 8-5x=-9x | | 0=4y-20 | | -6(n+3)-4=-2(n-3)4 | | 65-8x=17x | | -2(4+8x)=-6(3x-1) | | 12r+(-8)+(-12)= | | -7x=-30+3x | | (5x-3)-(2x-4)=-(x+3)-(x+5)+(x+3) | | 2b+4=-18-19 | | -2(2+8b)=-4(1+2b) | | 4x^2-16=2x+34 | | 7x-11=-19 | | -3(1+3k)=-3(6+4k) | | 3(4x-6)=-8(-x-2)+2 | | 23-5x=-27 | | -(-1-2n)=4-(n+5) | | 1.66666667p=2.66666667 |